LSQ14bdq: A Type Ic Super-luminous Supernova with a Double-peaked Light Curve - Nicholl M.; Smartt S. J.; Jerkstrand A.; Sim S. A.; Inserra C.; Anderson J. P.; Baltay C.; Benetti S.; Chambers K.; Chen T.-W.; Elias-Rosa N.; Feindt U.; et al. (IOP, 2022)
We present data for LSQ14bdq, a hydrogen-poor super-luminous supernova (SLSN) discovered by the La Silla QUEST survey and classified by the Public ESO Spectroscopic Survey of Transient Objects. The spectrum and light curve are very similar to slow-declining SLSNe such as PTF12dam. However, detections within ∼1 day after explosion show a bright and relatively fast initial peak, lasting for ∼15 days, prior to the usual slow rise to maximum light. The broader, main peak can be fit with either central engine or circumstellar interaction models. We discuss the implications of the precursor peak in the context of these models. It is too bright and narrow to be explained as a normal 56Ni-powered SN, and we suggest that interaction models may struggle to fit the two peaks simultaneously. We propose that the initial peak may arise from the post-shock cooling of extended stellar material, and reheating by a central engine drives the second peak. In this picture, we show that an explosion energy of ∼ 2× {10}52 erg and a progenitor radius of a few hundred solar radii would be required to power the early emission. The competing engine models involve rapidly spinning magnetars (neutron stars) or fallback onto a central black hole. The prompt energy required may favor the black hole scenario. The bright initial peak may be difficult to reconcile with a compact Wolf–Rayet star as a progenitor since the inferred energies and ejected masses become unphysical.